2021
DOI: 10.3390/polym13132146
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of 3D-Printed Interpenetrating Hydrogel Scaffolds for Promoting Chondrogenic Differentiation

Abstract: The limited self-healing ability of cartilage necessitates the application of alternative tissue engineering strategies for repairing the damaged tissue and restoring its normal function. Compared to conventional tissue engineering strategies, three-dimensional (3D) printing offers a greater potential for developing tissue-engineered scaffolds. Herein, we prepared a novel photocrosslinked printable cartilage ink comprising of polyethylene glycol diacrylate (PEGDA), gelatin methacryloyl (GelMA), and chondroitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…43 Similarly, Guan et al showed that BMSCs exhibited good adhesion, proliferation rate, and chondrogenic differentiation on CS-containing scaffolds. 44 These results indicated that the grafted oxidized CS onto GM hydrogel via Schiff base bond could significantly improve the ability of GM to promote the chondrogenic differentiation of BMSCs. 2.6.…”
Section: Gmocs Hydrogel Promoted the Chondrogenic Differentiation Of ...mentioning
confidence: 76%
See 1 more Smart Citation
“…43 Similarly, Guan et al showed that BMSCs exhibited good adhesion, proliferation rate, and chondrogenic differentiation on CS-containing scaffolds. 44 These results indicated that the grafted oxidized CS onto GM hydrogel via Schiff base bond could significantly improve the ability of GM to promote the chondrogenic differentiation of BMSCs. 2.6.…”
Section: Gmocs Hydrogel Promoted the Chondrogenic Differentiation Of ...mentioning
confidence: 76%
“…In addition, CS plays an important role in driving chondrogenic differentiation of bone marrow MSCs due to its glycans and sulfonic acid groups. , MSCs were coated with hydrogel scaffolds containing collagen-binding peptide CS (CS-SILY), resulting in higher expression of sulfated glycosaminoglycans . Similarly, Guan et al showed that BMSCs exhibited good adhesion, proliferation rate, and chondrogenic differentiation on CS-containing scaffolds . These results indicated that the grafted oxidized CS onto GM hydrogel via Schiff base bond could significantly improve the ability of GM to promote the chondrogenic differentiation of BMSCs.…”
Section: Resultsmentioning
confidence: 99%
“…HAMA ,, chondroitin sulfate-based hydrogel, and PU , hydrogels were also studied to mimic the cartilage layer of osteochondral tissue scaffolds. Since HAMA contains GAG, it holds high amounts of water and dissipates the energy during loading, which makes it suitable for osteochondral regeneration .…”
Section: Hydrogelsmentioning
confidence: 99%
“…Since HAMA contains GAG, it holds high amounts of water and dissipates the energy during loading, which makes it suitable for osteochondral regeneration . Since its mechanical properties are poor, it is usually used as an additive with GelMA or alginate hydrogels to improve chondrogenic potential, as mentioned in the previous section in detail. , Chondroitin sulfate also has poor mechanical properties, and it is used together with GelMA and PEGDA hydrogels to reduce immune response and improve cell viability and chondrogenic differentiation. …”
Section: Hydrogelsmentioning
confidence: 99%
See 1 more Smart Citation